TINJAUAN PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN GALIAN DAN TIMBUNAN JALAN DI RUAS TAPUS – MUARO SUNGAI LOlO STA.0 + 025 SAMPAI DENGAN STA.2 + 965 - Kurahman, Taufik; Eka Priana, Surya; Herista, Febrimen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Implementation of construction work using heavy equipment requires accurate planning so that a project can be achieved with optimal cost and implementation time. One of the important works in the Road Reconstruction Project in the Tapus – Muaro Sungai Lolo Section is Earthworks and Embankment Works. For this reason, it is necessary to select the right heavy equipment for the implementation of these jobs. Allocation, scheduling, and selection of equipment for each type of work is very important so that its operational capabilities can be optimal and mutually supportive of other equipment, bearing in mind that heavy equipment is very expensive and has a dominant contribution to the project, efficiency measures are urgently needed by utilizing the tool's resources. . This research was conducted by calculating the production capacity of each heavy equipment, in order to obtain its productivity value and the allocation of heavy equipment needed for the projects under review. This research was conducted using field observation methods and literature studies with reference to existing primary and secondary data. The number of heavy equipment needed in the Excavation and Stockpiling Project on Jalan Tapus – Muaro Sungai Lolo Section for Excavators is used 1 unit, Dump Trucks are used 6 units, Motor Graders are used 1 unit, Vibratory Rollers are used 1 unit. The total operational cost of using heavy equipment in the Excavation and Piling Project for the Tapus – Muaro Sungai Lolo Section is IDR.168,158,000, - With details for Excavators IDR.90,828,000, - Productivity 127,613 m3/hour, Dump Trucks IDR.38,860,000 ,- Productivity 103.32 m3/hour , Motor Grader IDR.22,150,000,- Overlay 96 m3/hour, Vibratory Roller IDR. 16,320,000,- Compaction 60.95 m3/hour. Keywords: heavy equipment, productivity, duration, number of tools, cost